Desegregation, the Learning Process, and Changing Values in Human Relations. Institute Interim Report - Strack, C. M.; Dahlstedt, W. A.; Henderson State Teachers Coll., ARadelphia, AR. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
The Institute was conducted from June 6, 1966 through July 8, 1966 by Henderson State Teachers College, which accepted forty-five participants in teams of three from each of fifteen school districts. The team consisted of a supervisor, a guidance person, and a language arts specialist or classroom teacher. Those participants nominated were considered potential leaders in the task to enhance effective education and desegregation. The Institute's objectives were as follows: (1) increase insight and understanding of multi-cultural contrasts and conditions present in desegregated classrooms; (2) increase ability to deal with language skills within the classroom; (3) become aware of own and other's attitudes, which condition and restrict teaching success; (4) reach a greater level of skill in formulating and applying corrective programs in the classroom; (5) examine evaluation procedures as related to a multi-cultural class; and, (6) assess possible gains from applying ideas of methodology, such as ungraded schools, team teaching, and more complete audio-visual procedures. (Author)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OEC-4-6-000107-1946.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Change; Cultural Differences; Curriculum Development; Educational Quality; Equal Education; Human Relations; Institutes (Training Programs); Intergroup Relations; Language Skills; Learning; Racial Relations; School Desegregation; Teacher Effectiveness; Arkansas